Impact of a tobacco smoke on a metabolism of an organ culture of bovine lenses and potential protection by antioxidants - Bormusov, E.; Reznick, A.Z. (Актуальні проблеми транспортної медицини, 2013)
Smoke from cigarette smoking (CS) has been proposed to be a major
environmental risk factor for a variety of human diseases and was implicated also in
cataract, an eye lens pacification, which is a major cause of blindness. We have undertaken
a study to investigate the effect of smoke on the physiological integrity and metabolism of
organ cultured lenses. Lenses in organ culture
are metabolically active and have functional
defense systems, thus they pr
ovide an appropriate model for studying the effects of smoke.
Also possible protective action of N-acetyl
L-cysteine (NAC) which is a precursor of
glutathione and the iron chelator Deferoxamine (DFO), was estimated as potential protective
agents against cataract. Предполагается, что
дым от курения сигарет (КС)
является основным экологическим фактором риска для развития множества
болезней человека и может также вызвать развитие катаракты, помутнения
хрусталика глаза, что является главной
причиной слепоты. Было проведено исследование для изучения воздействия
дыма на физиологич
ескую целостность
и метаболизм органной культуры хрусталиков глаза. Хрусталики глаза в органной
культуре метаболически активны и имеют функциональные системы защиты,
таким образом они являются оптимальной моделью для изучения воздействия
дыма. Также было оценено возможное
защитное действие N-ацетил L-цистеина (NAC), который является исходным
веществом для глутатиона и хелатирующего агента железа дефероксамина
(DFO) как потенциальных защитных веществ против катаракты. Передбачається, що дим від паління сигарет (ПС)
є основним екологічним фактором ризику для розвинення багатьох хвороб людини і може також викликати розвинення катаракти, помутніння кришталика
ока, що є головною причиною сліпоти.
Було проведено дослідження для вивчення впливу диму на фізіологічну цілісність
і метаболізм органної
культури кришталиків ока. Кришталики ока
в
органній культурі метаболічно активні та
мають функціональні системи захисту,
таким чином вони є оптимальною моделлю для вивчення впливу диму. Також була
оцінена можлива захисна дія N — ацетил — L- цистеїна (NAC), котрий є вихідною речовиною для глутатіона та хелатируючого агента заліза дефероксаміна
(DFO) як потенційних захисних речовин
проти катаракти.